2005
DOI: 10.1177/0733464805278378
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computer Input Devices by Older Adults

Abstract: A sample of 85 seniors was given experience (10 trials) playing two computer tasks using four input devices (touch screen, enlarged mouse [EZ Ball], mouse, and touch pad). Performance measures assessed both accuracy and time to complete components of the game for these devices. As well, participants completed a survey where they evaluated each of the devices. Seniors also completed a series of measures assessing visual memory, visual perception, motor coordination, and motor dexterity. Overall, previous experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 11 publications
3
55
0
3
Order By: Relevance
“…In line with previous research (see, e.g., [8]), we found evidence of the effect that a deterioration of the sense of touch can have on older adults' interaction with tabletops: Some participants were less effective in moving cards over the tabletop because they pressed either too hard or too 1 Given the generally excellent dragging performance with this type of touchscreen (cf. Section 2), this problem seems unlikely to be due primarily to the technology itself.…”
Section: Manipulation Problems and Their Consequencessupporting
confidence: 90%
“…In line with previous research (see, e.g., [8]), we found evidence of the effect that a deterioration of the sense of touch can have on older adults' interaction with tabletops: Some participants were less effective in moving cards over the tabletop because they pressed either too hard or too 1 Given the generally excellent dragging performance with this type of touchscreen (cf. Section 2), this problem seems unlikely to be due primarily to the technology itself.…”
Section: Manipulation Problems and Their Consequencessupporting
confidence: 90%
“…Experiments made at the Department of Psychology, Wilfrid Laurier University, in Canada 2005, confirmed that ''Overall, previous experience with computers had a significant impact on the type of device that yielded the highest accuracy and speed performance'' [52], p. 419.…”
Section: Symbol Recognitionmentioning
confidence: 51%
“…These diagnoses often result in both physical and perceptual impairments. Both typing and mouse use require good perceptual and cognitive abilities (17,38). The slower peripheral device use reported in the Dumont study may be due to cognitive and perceptual impairments as well physical ones.…”
Section: Discussionmentioning
confidence: 99%